Military operations in Afganistan and international humanitarian law - Christian Schaller (Stiftung Wissenschaft und Politik (SWP), 2010)
Until recently, German officials denied that the Bundeswehr was at war in Afghanistan, insisting that its role was to stabilize rather than to fight. In November 2009, Federal Minister of Defense Karl-Theodor Freiherr zu Guttenberg first referred to »warlike circumstances« and described the situation as a »non-international armed conflict« taking place in parts of Afghanistan. This position was now specified by Federal Foreign Minister Guido Westerwelle, who in an official government address to the German Bundestag stated that even the situation in the north of Afghanistan was to be qualified as an armed conflict within the meaning of international humanitarian law. But the search for appropriate terminology is much more than a matter of clear communication. It is above all a question of maximizing legal security for the forces on the ground
Keywords: 320